2018
DOI: 10.1177/0954406218796043
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the performance of the mixed flow and radial flow variable geometry turbines for an automotive turbocharger

Abstract: A new design of a mixed flow variable geometry turbine is developed for the turbocharger used in diesel engines having the cylinder capacity from 1.0 to 1.5 L. An equivalent size radial flow variable geometry turbine is considered as the reference for the purpose of bench-marking. For both the radial and mixed flow turbines, turbocharger components are manufactured and a test rig is developed with them to carry out performance analysis. Steady-state turbine experiments are conducted with various openings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Even though that like-engine waveforms were well replicated through implemented solenoid-controlled valves at turbine and compressor boundaries, their study presented a major drawback that they used the air as a working fluid which can yield to an increasing uncertainty of the predicted turbocharger characteristics as it strongly depends on the thermodynamic properties of the working gas such as the specific calorific value. The same observation about the susceptible irrelevance of working gas was marked for the experimental work of Ramesh et al 18 where smallscale mixed and radial turbocharger turbines were studied. Their study revealed the advantage of higher efficiency of the mixed flow turbine more than 25% compared to the radial turbine.…”
Section: Introductionsupporting
confidence: 52%
“…Even though that like-engine waveforms were well replicated through implemented solenoid-controlled valves at turbine and compressor boundaries, their study presented a major drawback that they used the air as a working fluid which can yield to an increasing uncertainty of the predicted turbocharger characteristics as it strongly depends on the thermodynamic properties of the working gas such as the specific calorific value. The same observation about the susceptible irrelevance of working gas was marked for the experimental work of Ramesh et al 18 where smallscale mixed and radial turbocharger turbines were studied. Their study revealed the advantage of higher efficiency of the mixed flow turbine more than 25% compared to the radial turbine.…”
Section: Introductionsupporting
confidence: 52%
“…The basic experimental test facility for steady state testing and its operating principle were discussed in detail by the authors in their previous paper, Ramesh et al. 6 Figure 5 shows the schematic of the cold air test rig with incorporating the features for conducting the transient response tests. For the transient tests, the quick-release on/off valve (QRV) is installed before the turbine inlet and its actuating system is marked within the dotted line.…”
Section: Experimental Test Set-up For Transient Response Testmentioning
confidence: 99%
“…The variation of turbine mass flow parameter (MFP) with turbine expansion ratio for different nozzle vanes opening can be referred from the authors’ previous work, figure 7 of Ramesh et al. 6…”
Section: Steady State Performancementioning
confidence: 99%
See 2 more Smart Citations